A Study on Hospitality Education at University : Jal’s Philosophy Education as an Example - Fujishima, Kiyohito (Bright Institute, 2021)
From the viewpoint of hospitality management, which has received particular attention in recent years, this paper considers it at the point of employee education. In recent years in Japan's industrial world, almost all fields are concerned about the importance of hospitality. Indeed, holding the 2020 Tokyo Olympic Games is spurring the momentum. Against this background, in this paper the author studied what kinds of education can be assumed for fostering qualities that can demonstrate hospitality, and examined measures to train hospitality minds in education conducted in university. As a reference example, the author introduced JAL's